β1 and β3 subunits amplify mechanosensitivity of the cardiac voltage-gated sodium channel Nav1.5 - Maroni, Michele; Körner, Jannis; Schüttler, Jürgen; Winner, Beate; Lampert, Angelika; Eberhardt, Esther (Pflügers Archiv: European Journal of Physiology, 2019)
In cardiomyocytes, electrical activity is coupled to cellular contraction, thus exposing all proteins expressed in the sarcolemma to mechanical stress. The voltage-gated sodium channel Nav1.5 is the main contributor to the rising phase of the action potential in the heart. There is growing evidence that gating and kinetics of Nav1.5 are modulated by mechanical forces and pathogenic variants that affect mechanosensitivity have been linked to arrhythmias. Recently, the sodium channel β1 subunit has been described to stabilise gating against mechanical stress of Nav1.7 expressed in neurons. Here, we tested the effect of β1 and β3 subunits on mechanosensitivity of the cardiac Nav1.5. β1 amplifies stress-induced shifts of V1/2 of steady-state fast inactivation to hyperpolarised potentials (ΔV1/2: 6.2 mV without and 10.7 mV with β1 co-expression). β3, on the other hand, almost doubles stress-induced speeding of time to sodium current transient peak (Δtime to peak at − 30 mV: 0.19 ms without and 0.37 ms with β3 co-expression). Our findings may indicate that in cardiomyocytes, the interdependence of electrical activity and contraction is used as a means of fine tuning cardiac sodium channel function, allowing quicker but more strongly inactivating sodium currents under conditions of increased mechanical stress. This regulation may help to shorten action potential duration during tachycardia, to prevent re-entry phenomena and thus arrhythmias.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Cardiac ion channel; Mechanosensitivity; Patch-clamp; Sodium channel